Entrepreneurial Ecosystem, Entrepreneurial Activity and Economic Performance - Kanza Sohail Khanani (Jurnal Inovasi Bisnis dan Kewirausahaan, 2019)
In this research, we have empirically tested the impact of Entrepreneurial Framework Conditions (EFC) on entrepreneurial activity and ultimately on economic growth of a nation. In our sample all the 54 countries participating in the GEM study in 2017 are taken. 67.8% of the world’s population and 86.0% of the world’s GDP is represented by the economies included in GEM 2017. The entrepreneurial ecosystem is captured through 12 EFCs used in the GEM model that includes: Financial environment, government policy of support and relevance, government policy of taxes and bureaucracy, government programs, entrepreneurial education at school stage and post school stage, R&D transfer, commercial and legal infrastructure, internal market dynamics, access to physical infrastructure, and social and cultural norms. The impact of these EFCs and their significance in creating entrepreneurial activity (TEA) in a nation is analyzed using OLS estimation technique with TEA as dependent variable. Secondly, the impact of entrepreneurial activity (TEA) on economic growth ( ∆GDP) is estimated using OLS regression model with control variables such as global competitiveness index (GCI) and Gross national income per capita, expressed in purchasing power parity (GNIC). The results suggest that entrepreneurship education at post school stage, entry burdens and cultural and social norms are significant framework conditions that support entrepreneurial activity, while R&D transfer, internal market dynamics and commercial and legal infrastructure hinders the process of entrepreneurship. Furthermore, TEA is significantly contributing to the economic growth of factor driven and efficiency driven economies.